Anticipation of Scheduled Feeding in BTBR Mice Reveals Independence and Interactions Between the Light- and Food-Entrainable Circadian Clocks - Vijaya Shankara, Jhenkruthi; Mistlberger, Ralph E.; Antle, Michael C. (Frontiers in Integrative Neuroscience, 2022)
Many animal species exhibit food-anticipatory activity (FAA) when fed at a fixed time of day. FAA exhibits properties of a daily rhythm controlled by food-entrainable circadian oscillators (FEOs). Lesion studies indicate that FEOs are separate from the light-entrainable circadian pacemaker (LEP) located in the suprachiasmatic nucleus. While anatomically distinct, food- and light-entrainable clocks do appear to interact, and the output of these clocks may be modulated by their phase relation. We report here an analysis of FAA in the BTBR T+ Itpr3tf/J (BTBR) mouse strain that provides new insights into the nature of interactions between food- and light-entrained clocks and rhythms. BTBR mice fed ad-libitum exhibit an unusually short active phase and free running circadian periodicity (~22.5h). In a light-dark cycle, BTBR mice limited to a 4h daily meal in the light period show robust FAA compared to C57BL/6J mice. In constant darkness, BTBR mice exhibit clear and distinct freerunning and food-anticipatory rhythms that interact in a phase-dependent fashion. The freerunning rhythm exhibits phase advances when FAA occurs in the mid-to-late rest phase of the free-run, and phase delays when FAA occurs in the late active phase. A phase-response curve (PRC) inferred from these shifts is similar to the PRC for activity-induced phase shifts in nocturnal rodents, suggesting that the effects of feeding schedules on the LEP in constant darkness are mediated by FAA. A phase-dependent effect of the freerunning rhythm on FAA was evident on both its magnitude and duration; FAA counts were greatest when FAA occurred during the active phase of the freerunning rhythm. The LEP inhibited FAA when FAA occurred at the end of the subjective day. These findings provide evidence for interactions between food- and light-entrainable circadian clocks and rhythms and demonstrate the utility of the BTBR mouse model in probing these interactions.